Numerical simulation of a passive heave compensator for scientific research ships - Persaud, Rudolph; Li, Hao Jie; Leng, Jian Xing (Journal of Naval Architecture and Marine Engineering, 2019)
Research vessels are commonly used on a daily basis for ocean exploration and payload handling. However, due to unpredictable wave motion on the ship and the flexibility of the cable, the heave of the ship is unavoidable and causes danger during operations, loss of payload, possible damages to expensive equipment and prolong period of downtime. A compensator system is an essential part of operations to mitigate this effect and to ensure safety, reduce down-time of operation and increase efficiency while providing longer and better duration of operation even in harsh conditions. In this article, a passive heave compensator system with cylinder, accumulator and depth compensator connected in series by pressured pipes developed for a scientific research ship with length of 68m and breath of 16m is analyzed along the coast of Guyana, South America. The payload used in this analysis is 200 ton. The working principle of the heave compensation system is described, the parameters affecting the performance of the system are simulated and analyzed using MatLab. A 3D model of the system is built using SolidWorks and schematic drawings are produced from AutoCAD. The compensation rate of the system is higher than 77% under the influence of the input wave and the system has a response of an average setting time of 18s. The point of maximum load exerted is at the splash zone. For a typical most probable extreme significant wave height, Hs= 2.3m, period T= 6s and direction μ= 45° in the operational area, the reduction in heave motion when the vessel is equipped with the heave compensator is approximately 77% compared to 47% reduction when the vessel is without a compensator.